2020
DOI: 10.3989/gya.1061182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of smoking processes on the nutritional value and fatty acid composition of Zander fish (<em>Sander lucioperca</em>)

Abstract: This study aimed to estimate the nutritional quality of Sander lucioperca fillets and alterations in lipid quality following hot and cold smoking processes. Our results revealed that the total fat content of zander fillets was 1.86 g/100g. Polyunsaturated fatty acids (PUFAs) were higher than saturated and monounsaturated fatty acids in fresh tissue samples. Arachidonic, docosahexaenoic and eicosapentaenoic acids were the most abundant PUFAs. Differences in the fatty acid compositions of the smoked and fresh fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 18 publications
3
12
0
Order By: Relevance
“…The SFA contents increased signi cantly after the smoking process for all the tested storage periods and this was closely related to the increases of C14:0, C16:0 and C18:0, which were higher than those of fresh zander sh [1]. The same for most MUFA and PUFA, which was mainly due to water loss by evaporation during both hot and cold smoking [1].…”
Section: Totalmentioning
confidence: 83%
See 2 more Smart Citations
“…The SFA contents increased signi cantly after the smoking process for all the tested storage periods and this was closely related to the increases of C14:0, C16:0 and C18:0, which were higher than those of fresh zander sh [1]. The same for most MUFA and PUFA, which was mainly due to water loss by evaporation during both hot and cold smoking [1].…”
Section: Totalmentioning
confidence: 83%
“…This process of thermal treatment of llets was conducted according to the following sequence: pre-drying of sh surface at 50-60 °C for 150 min, then hot smoking at 65-70 °C for 30 min and nally, steaming to obtain a temperature of 68-72°C. Oak wood was used for both smoking processes [1]. Finally, the llets were chilled by cold air at 10°C.…”
Section: Polyphenols Extractmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the wild and farmed fish used in the present study had a lower fat content than that noted by other authors. Bouriga et al [ 7 ] reported that the fat content in wild pikeperch was 1.9%, whereas protein was 17.7% and ash was 1.1%. A higher protein content, similar to that noted in the present study, was found by Çağlak and Karsli [ 24 ] in wild pikeperch (from 17.8% to 19.4% regarding of the season, for spring and autumn, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…However, a high-temperature treatment might negatively affect the nutritional profile of fish products. Bouriga et al [ 7 ], who applied hot smoking to increase a consumer acceptability of pikeperch fillets, noted that it decreased PUFA proportion, which is vitally important from a nutritional perspective, and promoted lipoperoxidation and lipid oxidation in the fillets. Easy to conduct in household conditions, pan-frying generally produces higher changes in the fish lipid composition than other cooking methods, which are manifested in higher losses of DHA (docosahexaenoic) and EPA (eicosapentaenoic) compared to other cooking methods [ 8 ].…”
Section: Introductionmentioning
confidence: 99%